INTERAKSI MASYARAKAT PADA RUANG PUBLIK DI DESA PASIE PINANG - supriadi supriadi (Prodi Sosiologi FISIP Universitas Teuku Umar, 2019)
The process of social interaction is an element of the communication process, where the two are closely interrelated. The process of social interaction can be built if the communication process is also effective between individuals and individuals, individuals and groups, groups and groups. As time goes by, global competition, all in an all-sophisticated era, social interaction can also be done indirectly by interacting through social media or in other words interacting online. Social media can be said as a medium used to communicate without face to face. The purpose of this research is to know how the process of interaction that occurs between the users of social media users and those who do not use social media in a public space. The method used in this study is a qualitative method with a descriptive approach. The data source consists of primary data and secondary data. Data collection techniques using interviews and documentation. while the analysis technique consists of data reduction, data presentation and data vertification. From the results of this determination show that interaction on social media is more active in comparison with direct or face-to-face interaction is caused by the influence of the internet or wifi network which greatly affects the patterns of interaction between communities, it is caused because most of the people who come to an public space is not solely for visiting, relaxing or just for coffeebut by instilling an intention to use the wifi that has been provided.